The International Classification of Functioning, Disability and Health: development of capacity and performance scales. - Almansa, J; Ayuso-Mateos, J; Garin, O; Chatterji, S; Kostanjsek, N; Alonso, J; Valderas, J; Cieza, A; Raggi, A; Svestkova, O; Burger, H; Racca, V; et al. (2011)
OBJECTIVE: There has been no attempt to obtain a continuous summary measure of disability from the checklist of the International Classification of Functioning, Disability and Health (ICF). Our objective was to assess whether valid scales of Capacity and Performance could be developed from the "Activities and Participation" domain of the ICF checklist. STUDY DESIGN AND SETTING: A multicenter, observational study of 1,092 patients with 12 different chronic conditions from five European countries was conducted. Exploratory and confirmatory factor analyses were performed to assess the underlying factor structure. Reliability and validity of the Capacity and Performance scales were evaluated. Construct validity was assessed calculating effect size coefficients between extreme severity groups (discriminant ability). RESULTS: The good fit of the confirmatory factor model supported the global scales of Capacity and Performance and their "Psychosocial" and "Physical" subscales. Reliability was excellent (coefficients=0.79-0.92). Effect sizes of most conditions were large for the Capacity global scale (0.50-3.05), and slightly lower for the Performance global scale (0.45-2.57). CONCLUSIONS: Our findings support the measurement model, reliability, and validity of the Capacity and Performance scales. Summary measures of functioning based on the ICF can be obtained using these scales, which should facilitate their incorporation in clinical and epidemiological studies.